Increased infiltration of regulatory T cells in hepatocellular carcinoma of patients with hepatitis B virus pre-S2 mutant - Teng, Chiao-Fang (Sci Rep, 2021)
Hepatocellular carcinoma (HCC) is a frequent and deadly human cancer worldwide that is intimately associated with chronic hepatitis B virus (HBV) infection. Pre-S2 mutant is a HBV oncoprotein that plays important roles in HCC development and is linked to poor prognosis in HCC patients. However, the profiles of tumor-infiltrating lymphocytes in HCC tissues of pre-S2 mutant-positive patients remain unknown. In this study, we performed fluorescent immunohistochemistry staining to detect the infiltration of ‘anti-tumor’ cytotoxic T lymphocytes (CTLs) and ‘pro-tumor’ regulatory T cells (Tregs) in pre-S2 mutant-positive and -negative HCC patients. We showed that pre-S2 mutant-positive patients had a significantly higher infiltration of CD4(+)CD25(+) cells and forkhead box P3 (Foxp3)-expressing cells but similar CTLs and lower granzyme B-expressing cells in HCC tissues compared with pre-S2 mutant-negative patients. Moreover, the percentage of pre-S2 plus pre-S1 + pre-S2 deletion (pre-S2 mutant) was positively correlated with the density of CD4(+)CD25(+) cells and Foxp3-expressing cells but negatively with granzyme B-expressing cells in HCC tissues. Considering that increased intratumoral Tregs have been shown to promote tumor immune evasion, our data may provide new insights into the pathogenesis of HBV pre-S2 mutant-induced HCC and suggest that therapeutics targeting Tregs may be a promising strategy for treating pre-S2 mutant-positive high-risk patient population.